Cluster-type models in the logistics industry - Nyrkov, Anatoliy; Sokolov, Sergei; Karpina, Anna; Chernyakov, Alex; Gaskarov, Vagiz (International Journal of Engineering and Technology, 2018)
The aim of the present article is to detect the basic principles of secure electronic document circulation (EDCS) systems for multi-location structure with multiple non-uniform connections. As far as the object of research is concerned, transport-logistical clusters are used. It is heterogeneous system with implicit classification. In the article were examined the basic stages of designing, methods and models of information security in electronic document circulation systems, operating in distributed network and interacting with other informational systems. The article contains analysis of regulatory and legal base in information security field of Russian Federation. The model of cluster information flows has been created for research purposes, based on hierarchical interaction model of transport-logistical cluster components. We describe transport-logistical cluster subjects, categorized information and supposed information assets. Based on potential threats and system vulnerabilities, mechanisms of EDCS information security have been described. EDCS data exchange process with another system, containing personal data has been described. As a result, a comprehensive set of measures was formed as well as information security tools based on requirements for data protection of personal data, and automated control systemsand transport-logistical cluster information systems at critical objects.
Keywords: Transport and Logistics Clusters; Electronic Document Workflow Systems; Information Security; Distributed Systems Architecture.